Effect of Active Teaching on Active and Informal Learning - saloua, bani khalfa (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The active participation of students is an inherent requirement of any educational intervention. Indeed, active teaching and working in subgroups is a method which promotes motivation among students in active informal learning. In this study, we have shown that the subgroups work, as a means of active learning, has improved student performance as well as a self-efficacy to control the content.